An Exploration of the Viral Coverage of Mosquito Viromes Using Meta-Viromic Sequencing: A Systematic Review and Meta-Analysis - Shenglin Chen; Yuan Fang; Ryosuke Fujita; Emad I. M. Khater; Yuanyuan Li; Wenya Wang; Peijun Qian; Lulu Huang; Zhaoyu Guo; Yi Zhang; Shizhu Li (Microorganisms)
The aim of this review was to delve into the extent of mosquito virome coverage (proportion of viral reads) via meta-viromic sequencing and uncover potential factors of heterogeneity that could impact this coverage. Data sources were PubMed, Web of Science, Embase, Scopus, Science-Direct, Google Scholar, and the China National Knowledge Infrastructure. Pooled coverage was estimated using random-effects modeling, and subgroup analyses further reveal potential heterogeneous factors. Within the three mosquito genera studied, Culex exhibited the highest pooled viral coverage of mosquito viromes at 7.09% (95% CI: 3.44–11.91%), followed by Anopheles at 5.28% (95% CI: 0.45–14.93%), and Aedes at 2.11% (95% CI: 0.58–7.66%). Subgroup analyses showed that multiple processing methods significantly affected the viral coverage of mosquito viromes, especially pre-treatment of mosquito samples with saline buffer/medium and antibiotics prior to DNase/RNase treatment and removal of the host genome prior to RNA library construction. In conclusion, the results of this study demonstrate that the viral coverage of mosquito viromes varies between mosquito genera and that pre-treatment of mosquito samples with saline buffer/medium and antibiotics before DNase/RNase treatment and removing host genomes prior to RNA library construction are critical for the detection of RNA viruses in mosquito vectors using meta-viromic sequencing.